APPLICATION OF NISBAH FUNCTION IN ELECTRODYNAMICS - Bambang Ruwanto; Maryanto Maryanto (Jurnal Penelitian Saintek, 2002)
Analyzes    about    characteristics    of    quotient   function Q(x) = (1- x)/(l  + x)  have been done, where x was scalar variable.  The result  of  the  analyzes showed  that  quotient function had inverse character and it can be developedfor two variables of multiplication or more. Application of quotient function   in  electrodynamics for   calculation  of  reflection coefficient on reflection wave on boundary plane produces simpleformulation for  r TE  and r TM.    The result is very useful, because mathematics calculation can be done easily.